1999
DOI: 10.1177/1350507699302004
|View full text |Cite
|
Sign up to set email alerts
|

The Many Faces of Action Learning

Abstract: Action Learning draws its roots from different philosophies of learning and change, which in turn, influence its design and practice. This article identifies common factors and differences among three different 'schools' of practice (Scientific, Experiential and Critical Reflection). It then distinguishes Action Learning from the other action approaches in this volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
176
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(179 citation statements)
references
References 12 publications
0
176
0
3
Order By: Relevance
“…Although the most common use of action learning is that participants from a range of different organisations meet to help one another tackle their individual issues (Pedler, Burgoyne, and Brook 2005) it is an approach that is also used to enable teams tackle problems and issues they have in common (Edmonstone and Flanagan 2007;Marsick and O'Neil 1999;Rigg 2008). In this project, it was planned to use action learning in two contexts.…”
Section: Three Methodsologies For Learning and Inquirymentioning
confidence: 99%
“…Although the most common use of action learning is that participants from a range of different organisations meet to help one another tackle their individual issues (Pedler, Burgoyne, and Brook 2005) it is an approach that is also used to enable teams tackle problems and issues they have in common (Edmonstone and Flanagan 2007;Marsick and O'Neil 1999;Rigg 2008). In this project, it was planned to use action learning in two contexts.…”
Section: Three Methodsologies For Learning and Inquirymentioning
confidence: 99%
“…The project requires students to form into self selected groups of four to six which establish the action learning group. In accordance with the principles of action learning (Pedler, 1997;Marsick & O'Neil, 1999), it is the responsibility of the groups to identify a suitable host organisation and with the host, negotiate the exact focus of the problem to be tackled. It is important to note that the project involves the progression of a real problem not simply one manufactured for the set (McGill and Beaty, 1995).…”
Section: Project Definitionmentioning
confidence: 99%
“…This management development technique deploys a relational view of learning and attempts to create communities of practice in which the construction of identities is enabled simply by being a part of the system of relations which are produced by social communities (Lave and Wenger, 1991:53) Action learning as a term is, however, used to define a wide variety of management development practice. For some, its use is synonymous with approaches that might be appropriately used to describe 'active learning'; for others, when it is the method that is emphasised, the focus moves to stress self-managed learning yet for others, action learning cannot be action learning unless a Revansesque or 'Scientific' (Marsick and O'Neil, 1999) approach is followed (Anderson and Thorpe, 2007). Pedler (1991) offers the following definition:…”
Section: Action Learningmentioning
confidence: 99%
“…These problems do not have clear solutions and are not puzzles, which are susceptible to expert advice. Through social interaction, team members take advantage of alternative views on their problem; therefore, learning occurs as a function of the experience within the group and not from an external source (Marsick and O'Neil, 1999). Revans (1980:256-7) suggested that:…”
mentioning
confidence: 99%